Mapas y clasificación de vegetación en ecosistemas estacionales: un análisis cuantitativo de los bosques secos de Piura - La Torre Cuadros, María de los Ángeles (2008)
We studied data from 65 0.1-hectare floristic inventories from the seasonal lowland vegetation in coastal Piura by using multivariate methods and analyses of floristic composition. We identified six vegetation groups, five of which greatly coincide with vegetation types already described 100 years ago by August Weberbauer. In contrast, we were not able to accurately identify any of the eight dry forest categories recently defined by the Proyecto Algarrobo for the study area using numerical methods. We conclude that the maps and data generated by Weberbauer are more accurate and better reveal the floristic relationships of the seasonally dry vegetation in Piura. Therefore, we suggest a more widespread use of the descriptions made by Weberbauer in the region, parallel to those of the Proyecto Algarrobo